Analisis Implementasi Layanan Customer Service Berbasis Digital Contact Center 172 Meningkatkan Responsivitas Pelayanan di Bandar Udara Internasional Adi Soemarmo Boyolali - Alfano Bagus Gumelar; Rosiana Ulfa (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The advancement of digital technology has encouraged the transformation of airport services, including the implementation of Customer Service through Contact Center 172. This study aims to analyze the implementation of Contact Center 172 in improving service responsiveness at Adi Soemarmo International Airport, Boyolali. The study employed a descriptive qualitative approach with a case study method. Data were collected through observation, interviews with five informants, and documentation, and analyzed using the Miles and Huberman interactive analysis model consisting of data collection, data reduction, data display, and conclusion drawing. The findings indicate that the implementation of Contact Center 172 has supported digital service transformation through an integrated communication system that facilitates real-time information delivery and complaint handling. The service has improved Customer Service responsiveness by providing easier access to information, faster response times, and more effective coordination among service units. Supporting factors include competent human resources, integrated systems, and adequate digital facilities, while the main obstacles involve limited internet connectivity, system maintenance disruptions, high complaint volumes, and limited user understanding of digital services. Therefore, strengthening technological infrastructure, improving staff competencies, and increasing public awareness are essential to optimize digital-based airport services.